2007
DOI: 10.1161/circresaha.106.144006
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Mediated Endothelial Progenitor Cell Biology and Kinetics For Physiological Postnatal Vasculogenesis

Abstract: Abstract-Estrogen has been demonstrated to promote therapeutic reendothelialization after vascular injury by bone marrow (BM)-derived endothelial progenitor cell (EPC) mobilization and phenotypic modulation. We investigated the primary hypothesis that estrogen regulates physiological postnatal vasculogenesis by modulating bioactivity of BMderived EPCs through the estrogen receptor (ER), in cyclic hormonally regulated endometrial neovascularization. Cultured human EPCs from peripheral blood mononuclear cells (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 37 publications
4
107
1
Order By: Relevance
“…There is also evidence illustrating an important role for endothelial progenitor cells in endometrial angiogenesis, with several studies demonstrating the presence of donor-derived endothelial cells within the uterus after bone marrow transplant from either male mice or transgenic mice with endothelial cell-specific mutations (Asahara et al 1999, Masuda et al 2007, Mints et al 2008. In a human study, endothelial cells with an XY genotype were detected in the endometrium of a women receiving an allogenic transplant with bone marrow derived from a male (Mints et al 2008).…”
Section: Endometrial Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence illustrating an important role for endothelial progenitor cells in endometrial angiogenesis, with several studies demonstrating the presence of donor-derived endothelial cells within the uterus after bone marrow transplant from either male mice or transgenic mice with endothelial cell-specific mutations (Asahara et al 1999, Masuda et al 2007, Mints et al 2008. In a human study, endothelial cells with an XY genotype were detected in the endometrium of a women receiving an allogenic transplant with bone marrow derived from a male (Mints et al 2008).…”
Section: Endometrial Angiogenesismentioning
confidence: 99%
“…The extent of endothelial progenitor cell incorporation is influenced by circulating hormones. In a study by Masuda et al (2007), ovariectomised mice received a bone marrow transplant from transgenic mice expressing b-galactosidase under the regulation of the endothelial cell-specific promoter TIE2. In these animals, oestrogen, but not progesterone, treatment caused a significant increase in bone marrow-derived endothelial progenitor cells incorporated into the growing uterine vasculature.…”
Section: Endometrial Angiogenesismentioning
confidence: 99%
“…Sex steroids have an impact on stem cell populations of various types. Estrogens enhance self renewal of embryonic stem cells 29 , promote endothelial progenitor cells 30 and, during pregnancy, contribute to the expansion of hematopoietic stem cell populations 31 .…”
Section: Introduction (Epidemiology)mentioning
confidence: 99%
“…Estrogens have a well established pro-angiogenesis function, best known in the endometrium during the female reproductive cycle, which is mediated by enhancement of endothelial cell proliferation and migration 30,53 . This is mediated by diffusible factors like PAF 54 and VEGF 55 , which are frequently secreted by cancer cells in response to estrogens.…”
Section: Introduction (Epidemiology)mentioning
confidence: 99%
“…Apart from the local induction of endothelial growth factors, the underlying proposed mechanisms of E2 also include the ability of E2 to mobilize EPCs, which can incorporate into denuded carotid arteries, thereby participating in the regeneration of the neo-endothelium (3,4). We and others (3,14,16) have also shown that E2-mediated enhancement in the recovery from AMI involves ischemic cardiac neovascularization, reduction in fibrosis, and enhanced expression of angiogenic growth factors in OVX mice receiving estradiol that is, at least in part, due to mechanisms involving eNOS and/or MMP9-dependent EPC mobilization, homing, and inhibition of apoptosis. In another published study, using BM-transplantation models, we have demonstrated that following E2 supplementation, EPC mobilization and EPC-mediated cardiac repair is depressed significantly in mice lacking either ER␣ or ER␤ (15).…”
Section: Discussionmentioning
confidence: 99%